Technical report. Growing Up in Hungary - Cohort '18 Hungarian birth cohort study. Prenatal research, preparational phase - Zsuzsanna Veroszta (Hungarian Demographic Research Institute, 2018)
The Hungarian Central Statistical Office Demographic Research Institute launched a Hungarian birth cohort study entitled 'Cohort '18 - Growing Up in Hungary', which follows children born in 2018 and 2019. Data collection began during gestation following approximately 10,000 children born to women who were pregnant at the beginning of 2018. The children will be reevaluated at age six months, one year, and three years within the parameters of the project. The main objective of the study is to provide a comprehensive overview of child development and its influential factors in Hungary. The Cohort '18 Technical Report presents the details of the preparatory work that was necessary to begin the research. It presents the theoretical, methodological and organizational phases and steps prior to the first - prenatal - data collection phase.
Keywords: J12; J13; 300; Cohort '18; birth cohort study; pregnancy; health visitor; child development; Fertilität; Kohortenanalyse; Ungarn